HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN 3M PLUS PADA IBU RUMAH TANGGA DI KELURAHAN TANJUNG RANCING TAHUN 2022 - Devara Alya Danisa; Ridwan Ridwan; Khairil Anwar (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
Efforts to eradicate mosquito larvae in the work area of the Kutaraya Health Center in 2020 have an achievement of 66% and in the work area of the Kutaraya Health Center, there is the lowest subdistrict to eradicate mosquito larvae, namely Tanjung Rancing Village, which only reached 58%. The indicator was not successful because the target to be achieved for the indicator to eradicate mosquito larvae was 95% in accordance with the regulation of the minister of health number 50 of 2017. The purpose of this study was to determine the relationship between knowledge and attitudes with 3m plus action on housewives in Tanjung Rancing Village. This research is an analytic study with a cross sectional study approach. The sample in this study was 100 housewives. The sampling technique was proportional stratified random sampling. Data analysis is univariate analysis and bivariate analysis using Chi Square. Of the 100 housewife respondents, 59% had good knowledge, 51% had a negative attitude, and 53% had bad actions. The results of the Chi-Square statistical test obtained p value <0.05 (p = 0.001) meaning that there is a relationship between knowledge and 3m plus action and p <0.05 (p = 0.017) meaning that there is a relationship between attitude and 3m plus action, it can be concluded that there is a significant relationship between knowledge and attitudes with 3m plus actions on housewives in Tanjung Rancing Village.